Análise do efeito da ação do vento no projeto de edifícios altos de concreto para diferentes sistemas estruturais - Guerzoni, Rafael Grifoni (2020)
The construction of ever taller buildings challenges civil engineers to seek new solutions and structural systems that enable their projects. Ego seems to be the main reason for the construction of huge skyscrapers, which are not always economically justified. In their projects, horizontal loads assume a fundamental role in the design and analysis of the stability of the building. Foreign and Brazilian standards are based on the gust loading fator to estimate the dynamic response, considering wind-velocity and turbulence profile. Thus, this work presented a study of the structural behavior of a tall building submitted to horizontal and vertical loads, considering Brazilian, foreign and technical literature standards. This work was divided in three steps. The first one consisted of a comparative study among several standards, showing that the Brazilian one presented similar values to the others of longitudinal dynamic response due to wind loads on a tall building. The second one presented a case study of a tall building submitted to wind loads calculated according to Brazilian, American and European standards. Top floor displacement, inter-story drift and maximum acceleration results were obtained through software and used to verify serviceability state limit criteria. These analysis have showed that Brazilian standard limits are more rigorous in checking maximum displacement and acceleration, while the American standard presented higher values of inter-story drift. The third phase of this work presented a comparative study between three lateral-load resisting systems applied to a tall building: rigid frames, shear wall-frame interaction, and lateral bracing with steel cross frames. All three were able to resist wind loads. However, the use of shear wall-frame interaction system reduced by 15% the volume of concrete, while using the lateral bracing system it was possible to save 31% of concrete, compared to the rigid frame system. In addition, the analysis showed that the coefficient Ɣz of global stability resulted in a good approximation of the nonlinear global effects in the studied cases.